2012
DOI: 10.1182/blood-2011-10-387977
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting acute graft-versus-host disease effects of Tim-3/galectin-9 pathway blockade dependent upon the presence of donor regulatory T cells

Abstract: T-cell immunoglobulin mucin-3 (Tim-3) is expressed on pathogenic T cells, and its ligand galectin-9 (gal-9) is up-regulated in inflamed tissues. When Tim-3 ؉ T cells encounter high gal-9 levels, they are deleted. Tim-3 is up-regulated on activated T cells during GVHD. Inhibition of Tim-3/ gal-9 binding by infusion of a Tim-3-Ig fusion protein or Tim-3 ؊/؊ donor T cells increased T-cell proliferation and GVHD lethality. When the Tim-3/gal-9 pathway engagement was augmented using gal-9 transgenic recipients, GVH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 40 publications
3
40
0
Order By: Relevance
“…Our data (Supplemental Figure 4) showed that blocking TIM-3 shows a trend of making GVHD worse and blocking PD-1 indeed makes GVHD worse, in a fashion similar to CD70 deficiency in donor T cells. These data suggest that these immune checkpoint molecules do have a biological impact in our models, which are consistent with a few previous publications (3133). …”
Section: Resultssupporting
confidence: 94%
“…Our data (Supplemental Figure 4) showed that blocking TIM-3 shows a trend of making GVHD worse and blocking PD-1 indeed makes GVHD worse, in a fashion similar to CD70 deficiency in donor T cells. These data suggest that these immune checkpoint molecules do have a biological impact in our models, which are consistent with a few previous publications (3133). …”
Section: Resultssupporting
confidence: 94%
“…1,2 Other negative regulatory pathways have been shown to play an important role in regulating acute GVHD. [19][20][21][22] Because B7-H3 is a B7 homolog, similar to the PD-1/PD-L1 pathway, it is not surprising that during acute GVHD, B7-H3 would be upregulated in GVHD target organs and that the absence of this inhibitory receptor would accelerate GVHD. 23 Because B7-H3 2/2 donor T cells accelerated GVHD lethality, B7-H3 expression plays a cell-intrinsic role in suppressing T-cell responses.…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, these studies employed several different immune system challenges, including mouse models for autoimmunity and autoinflammation [6, 48-54], allotransplantation [55, 48, 56], tolerance induction [6, 48] and allergy [57, 58]. Thus, a substantial body of data has accumulated to support the conclusion that Tim-3 exerts a suppressive effect on Th1 cells.…”
Section: Regulation Of Cd4 T Cell Responses By Tim-3mentioning
confidence: 99%